Development of an innovative, high speed, large-scaled, and affordable metal additive manufacturing process. Issue 1 (2020) - Nguyen, Hoa Xuan; Suen, Hawke; Poudel, Bibek; Kwon, Patrick; Chung, Haseung
Abstract: This paper introduces a new additive manufacturing (AM) process which significantly improves the productivity of the current metal AM technologies by combining binder jet printing and stereolithography principles. Three dimensional objects can be printed on a powder bed system where photopolymerization takes place by selectively curing the suspensions containing metallic powder and ultraviolet curable resin in a layer-by-layer fashion. Integration of a digital light projection module allows a high-speed production with dimensional accuracy within 100 µm. Printed parts are sintered at appropriate temperatures to attain metal parts with the final density above 97% and homogenous microstructure without residual stress.